2020
DOI: 10.3390/cancers12010172
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Primary Breast Tumors Induce Supportive Premetastatic Changes in the Extracellular Matrix and Soluble Components of the Lung Microenvironment

Abstract: The lung is one of the deadliest sites of breast cancer metastasis, particularly in patients with triple-negative (TN) disease. We hypothesized that the presence of a TN primary breast tumor induces changes in the extracellular matrix (ECM) and soluble components of the lung microenvironment that support metastatic behavior. SUM159 (TN) and MCF7 (luminal A) breast cancer cells were injected into mice, and primary breast tumors were established prior to assessing metastatic niche changes. We observed increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…Furthermore, intratumor hypoxia at primary site promotes PMN formation in secondary organs through enhancement of the expression of several factors and the involvement of exosomes [ 200 , 201 ]. The role of exosomes and MVs from the primary tumor in the communication with PMN cells and modification of ECM has also been widely described [ 202 205 ]. Therefore, CSCs may play an important role in PMN formation, but further research is needed to clarify the specific role of the CSC secretome.…”
Section: Secretome In Metastasismentioning
confidence: 99%
“…Furthermore, intratumor hypoxia at primary site promotes PMN formation in secondary organs through enhancement of the expression of several factors and the involvement of exosomes [ 200 , 201 ]. The role of exosomes and MVs from the primary tumor in the communication with PMN cells and modification of ECM has also been widely described [ 202 205 ]. Therefore, CSCs may play an important role in PMN formation, but further research is needed to clarify the specific role of the CSC secretome.…”
Section: Secretome In Metastasismentioning
confidence: 99%
“…Growing evidence suggests that the primary tumor also primes distant organs in the development of a premetastatic niche to aid metastasis [10,11]. In mouse models, FN deposition is upregulated in premetastatic niches [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, EVs have been reported as a major cause of FN accumulation in the premetastatic niche. They have also been connected to the recruitment of tumor-supporting stromal cells and the enhanced attachment of disseminated tumor cells [10,19]. We recently demonstrated that conditioning pulmonary fibroblasts with EVs from BC cells could drastically alter the subsequent growth of epithelial BC cells in a FN-dependent manner [14].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), a collective term covering a variety of cell-derived membranous structures, can encapsulate and transport various cellular materials [4][5][6][7][8], mediating the crosstalk between primary tumour microenvironment and the PMN during the early stages of tumour metastasis [9,10]. Tumour-derived EVs can alter the microenvironment in future metastatic sites by directly targeting organ-specific resident cells (liver Kupffer cells [11][12][13][14], hepatic stellate cells (hStCs) [12,15], bone marrow stromal cells [16], tissue-resident macrophages [17,18], lung fibroblasts [14,15,[19][20][21][22][23], lung epithelial cells [14,24], brain astrocytes [19], neurons [19] and microglia [25]). In this way, EVs facilitate PMN formation through induction of cytokines, chemokines and growth factors, extracellular matrix (ECM) remodelling and metabolic reprogramming.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%